Horticultural Therapy Reduces Biomarkers of Immunosenescence and Inflammaging in Community-Dwelling Older Adults: A Feasibility Pilot Randomized Controlled Trial - Wong, Glenn Choon Lim (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: With the challenges that aging populations pose to health care, interventions that facilitate alleviation of age-related morbidities are imperative. A prominent risk factor for developing age-related morbidities is immunosenescence, characterized by increased chronic low-grade inflammation, resulting in T-cell exhaustion and senescence. Contact with nature and associated physical activities have been shown to boost immunity in older adults and may be promoted in the form of horticultural therapy (HT). We aimed to examine the effects of HT on immunosenescence. METHOD: We conducted a randomized controlled trial with 59 older adults assigned to either the HT intervention or waitlist control group. Older adults in the HT intervention group underwent HT intervention program over 6 months. Venous blood was drawn at baseline and at the third and sixth month from the commencement of this study. For participants who attended all 3 blood collection time points (HT: n = 22; waitlist: n = 24), flow cytometry analysis was performed on whole blood samples to evaluate the kinetics of lymphocyte subsets over the intervention period, revealing the composition of CD4(+) and CD8(+) subsets expressing exhaustion markers—CD57, CTLA4, and KLRG1. Enzyme-linked immunosorbent assays were employed to measure changes in plasma IL-6 levels. RESULTS: HT is associated with increased numbers of naive CD8(+) T cells and fewer CTLA4-expressing terminally differentiated effector CD4(+) and CD8(+) memory T cells re-expressing CD45RA (TEMRA). Furthermore, IL-6 levels were reduced during HT, and the frequencies of naive and TEMRA CD8(+) T cells were found to be associated with IL-6 levels. CONCLUSION: HT is associated with a reduction in the levels of biomarkers that measure the extent of T-cell exhaustion and inflammaging in older adults. The positive effects of HT on T-cell exhaustion were associated with the reduction of IL-6 levels.